2015
DOI: 10.1097/fjc.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Luteolin on Ischemia/Reperfusion Injury in Diabetic Rats Are Modulated by eNOS and the Mitochondrial Permeability Transition Pathway

Abstract: Myocardial ischemia/reperfusion (I/R) injury in diabetes is associated with oxidative stress, endothelial nitric oxide synthase (eNOS) dysfunction, and mitochondrial collapse, whereas luteolin is known to protect the cardiovascular system against diabetes and I/R injury. Here, we investigated whether luteolin pretreatment diminishes myocardial I/R injury in diabetic rats by affecting eNOS and the mitochondrial permeability transition pore (mPTP). After diabetic rats were produced by streptozotocin treatment (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 49 publications
(68 reference statements)
2
32
0
Order By: Relevance
“…Group A was the control group which was given normal saline, Group B was exposed to 300 ppm (300 mg/L) of NaF in drinking water daily for a week, Groups C and D were exposed to 300 ppm (300 mg/L) of NaF and concurrently administered Luteolin orally daily at a dosage of 100 and 200 mg/kg for the same time point. The dosage of Luteolin was chosen based on the previous studies but with slight modifications .…”
Section: Methodsmentioning
confidence: 99%
“…Group A was the control group which was given normal saline, Group B was exposed to 300 ppm (300 mg/L) of NaF in drinking water daily for a week, Groups C and D were exposed to 300 ppm (300 mg/L) of NaF and concurrently administered Luteolin orally daily at a dosage of 100 and 200 mg/kg for the same time point. The dosage of Luteolin was chosen based on the previous studies but with slight modifications .…”
Section: Methodsmentioning
confidence: 99%
“…Employing diabetic rats subjected to myocardial I/R, it has been assessed the protective effects of luteolin or breviscapine, a flavonoid extracted by Erigeron breviscapus . Luteolin (100 mg/kg/day intragastrically) or breviscapine (60 mg/kg orally) reduced the ROS production [165,166]. Luteolin also improved left ventricular function and cardiac tissue viability [165].…”
Section: In Vivo Effects Of Polyphenols Against Oxidative Stress-imentioning
confidence: 99%
“…Luteolin (100 mg/kg/day intragastrically) or breviscapine (60 mg/kg orally) reduced the ROS production [165,166]. Luteolin also improved left ventricular function and cardiac tissue viability [165]. In addition, breviscapine reduced the expression of ICAM-1 in rat myocardium, the inactivation of ATPase and associated ionic disturbances [166].…”
Section: In Vivo Effects Of Polyphenols Against Oxidative Stress-imentioning
confidence: 99%
“…Non-hypertensive doses of azilsartan have been reported to cardiac remodeling, infarct size and fibrotic changes after induction of myocardial infarction 28). It has been reported earlier that, eNOS dysfunction is one of the important pathways during myocardial I/R-injury 29). Wu et al4) have reported that PostC provides benefits in I/R-injury of heart by upregulation of eNOS.…”
Section: Discussionmentioning
confidence: 99%